Development of combined protein-fat emulsions for sausage and semifinished products with poultry meat - Пасічний, Василь Миколайович; Маринін, Андрій Іванович; Мороз, Олена Олексіївна; Гередчук, Аліна Михайлівна (Eastern-European Journal of Enterprise Technologies, 2015)
The research on the possibility to improve the rheological characteristics of standardized 1 and 2 % solutions of whey, modified potato starch and "Extra" starch when adding pyrogenic silica A300 to the system for further use of these ingredients in protein-fat emulsions for meat products is presented. The prospects of using combined protein-fat emulsions and protein-containing fillers of animal and vegetable origin in the production of sausages and semi-finished products from poultry meat were considered. It was revealed that the pyrogenic silica A300 at a concentration of 0.3% is able to significantly improve the effective viscosity of standardized solutions of modified potato starch and "Extra" starch and this effect increases after heat treatment of solutions. Using this effect has allowed to develop new types of combined protein-fat emulsions, which in an amount of 20...40 % enhance technological characteristics of poultry minced meat. The results allow to expand the possibilities of meat-processing enterprises to use poultry meat in technologies of sausage and semifinished products.